Efektivitas Latihan Range of Motion (ROM) Terhadap Kekuatan Otot Pada Penderita Stroke - Parmin, Selamat; Safitri, Serli Wulan; Morens, Devia (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Stroke is a condition that occurs when the blood supply to a part of the brain is suddenly disrupted, because some brain cells die due to impaired blood flow due to blockage or rupture of blood vessels in the brain. The purpose of this study was to determine the effect of "Range Of Motion with muscle strength in stroke patients at the Harapan Kita Social Home for the Elderly in Palembang City 2023". This Community Service uses a group of subjects who meet the criteria for Community Service in the intervention group. The sample of community service was 54 people from the population, the data collection technique used was a questionnaire, 30 respondents were given Range Of Motion intervention in a week. Based on the results of the analysis of muscle strength in the intervention group given ROM using the Paired Samples T-Test in the intervention group, a p value of 0.004 (p <0.05) was obtained, this shows that the intervention group has a significant effect between Range Of Motion on muscle strength in stroke patients. This shows that there is good effectiveness of Range Of Motion Therapy on Muscle Strength in Stroke Patients in the Harapan Kita Social Home for the Elderly in Palembang City. Based on the results of Community Service, there is an increase in muscle strength from Range Of Motion therapy. It is hoped that therapy can be carried out continuously so that a comfortable atmosphere can be created during the Range Of Motion therapy process.